UPAYA PENINGKATAN KUALITAS PEMBELAJARAN LOMPAT JAUH GAYA JONGKOK MELALUI STRATEGI PENDEKATAN PERMAINAN PADA SISWA: SMK NEGERI 1 PANJI SITUBONDO - SUHRI SUHRI (Mitra Pendidikan, 2022)
The formulation of the problem in this study: Is the method of the Game Approach in the Long Jump Squat style able to improve the quality and improve the learning outcomes of health sports in class X PMS 2 SMK Negeri 1 Panji Situbondo. The general objective of this research is to improve teaching and learning outcomes of health sports subjects, especially the long jump. The specific purpose of this research is to improve the quality of learning in the Squat style long jump with a game approach strategy in class X PMS 2 SMK Negeri 1 Panji Situbondo in the 2019/2020 academic year. This research is a class action research or Classroom Action Research that focuses on efforts to change the current real conditions in the expected direction. Kemmis and Mc Taggart (1988; 5) stated that; Action research is a form of collective self-reflective inquiry undertaken by participants in social situation in order to improve the rationality and justice of their own social or educational practice, as well as their understanding of these practices and situations in which these practices are carried out. This means that classroom action research is a form of self-reflection research conducted by participants in social situations to improve thinking skills in educational processes and practices as well as understanding of practices and situations where practice is carried out. This classroom action research is planned in three cycles, where in each cycle consists of 4 components, namely; stages of Planning (Planning), Implementation of action (Action), Observation (Observation) and Reflection (Reflection). Implementation of learning by using learning models long jump squat style with a game approach strategy. In the initial conditions / before the study there were 25% of students who were able to make a jump. After cycle 1 there are 35% of students who are able to make a jump. In the second cycle there was an increase of 65% of students who were able to jump and in the third cycle there were 80% of students who were able to jump. From the results of the study it can be concluded that; training through a game approach strategy can improve the quality of the squat-style long jump learning in class X PMS 2 students of SMK Negeri I Panji Situbondo for the 2019/2020 academic year.